Service Levels Analys in The Segment Street of Front Market Peterongan - Vera Mahardika; Iin Irawati; Bambang Tutuko (Universitas Dr. Soetomo, 2023)
Apart from parking lots, several things that trigger traffic problems at the Peterongan market are the presence of street vendors trading on the road, passengers getting on and off vehicles on the road, loading and unloading activities on the side of the road and pedestrians. These things are side obstacles that affect the performance of the front road segment of the Peterongan market. Based on this, this research is focused on analyzing the service level of the front road in the Peterongan market. The method used is MKJI 1997. The highest traffic flow value occurs on Monday at 06.00 – 07.00 at 5336.1 pcu/hour. The high traffic flow is caused at this time when going to school and work. The capacity value during the highest traffic flow conditions is 8834.76 pcu/hour. The Degree of Saturation (DS) value of the highest current and capacity value is 0.603989. The performance of the road in front of the Peterongan market is at Level of Service (LOS) D, which indicates that during peak hour traffic is in a saturated condition and is almost approaching the traffic jam threshold, namely 0.75